Automatic irrigation system / Muhamad Izzuddin Othman, Amirul Afiq Mohammad Shahar and Muhammad Iskandar Izzat Ismail - Othman, Muhamad Izzuddin; Mohammad Shahar, Amirul Afiq; Ismail, Muhammad Iskandar Izzat (2015)
Proper irrigation is vital for agriculture industry. Agriculture is one of the most important assets in every country. Agriculture is important especially for farmers because this is where they can earn income through agriculture. Nowadays, agriculture has been rapidly improved in terms of technology. The automated irrigation system is a very good device for every farmer because this device will operate when the soil is at dry state. This device will detect the soil moisture by using two iron rode. So, when the soil is at ‘wet’ state the device will do nothing. But, if the soil is at ‘dry’ state, it will on the water pump sensor and irrigated the plant until the soil is at ‘wet’ state. This is very convenience device because the farmers do not need to worry about their plant and checking their plants always because their plants are will not wilt easily due to the productivity of irrigation system. This device also used a solar energy. So, it will reduce cost and no electric consumptions are needed for this particular device.